The Impact of The Strategies of Individualized Instruction (Claire Plan) and Cooperative Learning (Jigsaw 2) on Students Achievement in The Principles of Pedagogy Course at The University of Zarqa in Jordan - Mohammad Saleem Alzboon; Rada Salamah Mawadieh; Murad Abdullah Mawajdeh; Baker Samih Al Mawajdeh (University of Science and Technology, Yemen, 2016)
Abstract                This study aimed to compare the impact of the    individualized instruction and cooperative learning  strategies on students' achievement for the course of the principles of pedagogy at the University of Zarqa in Jordan . The study sample composed of ( 288 ) students who were studying the course of principles of pedagogy in the academic year 2013/2014. The sample was chosen as an intentional sample. Students in the sample were distributed into (3) groups. The fist experimental group ( 92 students) was taught using individualized instruction (Claire Plan). The second experimental group ( 99 students) was taught  using cooperative learning (Jigsaw 2) strategy. The control group (97 students) was taught using the traditional way. After finishing teaching the three groups, the analysis of variance duo (3 × 2) was used to see the impact of the study variables ( the method and sex) in student achievement. The results found that the mean of achievement of students who were taught by the way of cooperative learning was better than means of those who were taught by the individualized instruction and the traditional methods.  The mean of students who taught by individualized instruction method was better than those who were taught by the traditional way. However, there was no significant difference in achievement is attributed to the sex nor the interaction between the teaching method and sex. The study concluded with a set of recommendations. Some of such recommendation are that staff in Jordanian universities should use the ways of individualized instruction (Claire Plan) and cooperative learning (Jigsaw 2) in teaching their courses. More studies should be conducted to look for the impact of the methods of individualized instruction (Claire Plan) and cooperative learning (Jigsaw 2) on the achievement in the emotional and self- kinesthetic areas. Further studies can be conducted to find out the material cost of the methods of individualized instruction (Claire Plan) and cooperative learning (Jigsaw 2) compared to the traditional way.